Strategi Pemasaran Benih Padi Studi Kasus di PT Bcg (Persero) Ubr V Kabupaten Lampung Timur - Dina Aprianti; Nurman Abdul Hakim; Dayang Berliana (Politeknik Negeri Lampung, 2019)
The author's goal is to identify internal factors in the form of strengths and weaknesses as well as external factors in the form of opportunities and threats in marketing rice seeds at PT BCG, analyzing the marketing strategies of rice seeds most appropriate to achieve the sales volume of rice seeds and expanding the distribution area at PT BCG. The data used are of two types, namely quantitative and qualitative data obtained directly. Results and discussion concluded that internal factors affecting rice seed marketing included strength factors, namely large land area and weaknesses, namely the number of human resources in production which were still lacking and were still done manually, while external marketing factors for opportunity factors were good support from surrounding communities in seed business for the welfare of farmers as consumers and the threat factor is competitors in the same business. Companies need to collaborate with fellow producers in meeting the needs of consumers, the company applies friendly and courteous servicesto consumers, the company needs the application of agricultural tools in producing seeds, the company needs to open a branch selling new products, the company is able to increase business capital, and the company uses packaging that is not easily damaged and airtight material (polyethylene plastic). determining the value or weight rating for strengths of 0.21, then weaknesses of 0.09 then opportunities of 0.26, and threats of 0.14.